But I Was So Sure! Metacognitive Judgments Are Less Accurate Given Prospectively than Retrospectively - Siedlecka, Marta; Paulewicz, Borysław; Wierzchoń, Michał (Frontiers in Psychology, 2016)
Prospective and retrospective metacognitive judgments have been studied extensively in the field of memory however their accuracy has not been systematically compared. Such a comparison is important for studying how metacognitive judgments are formed. Here, we present the results of an experiment aiming to investigate the relation between performance in an anagram task and the accuracy of prospective and retrospective confidence judgments. Participants worked on anagrams and were then asked to respond whether a presented word was the solution. They also rated their confidence, either before or after the response and either before or after seeing the suggested solution. The results showed that although response accuracy always correlated with confidence, this relationship was weaker when metacognitive judgements were given before the response. We discuss the theoretical and methodological implications of this finding for studies on metacognition and consciousness.